Joseph Riepel's Theory of metric and tonal order : phrase and form : a translation of his Anfangsgründe zur musicalischen Setzkunst, chapters 1 and 2 (1752/54, 1755) /: phrase and form : a translation of his Anfangsgründe zur musicalischen Setzkunst, chapters 1 and 2 (1752/54, 1755). ([2014]) - Riepel, Joseph, 1709-1782
No abstract available